A Narrative Review on Dietary Strategies to Provide Nitric Oxide as a Non-Drug Cardiovascular Disease Therapy: Beetroot Formulations—A Smart Nutritional Intervention - Diego dos Santos Baião; Davi Vieira Teixeira da Silva; Vania Margaret Flosi Paschoalin (Foods, 2021)
Beetroot is a remarkable vegetable, as its rich nitrate and bioactive compound contents ameliorate cardiovascular and metabolic functions by boosting nitric oxide synthesis and regulating gene expressions or modulating proteins and enzyme activities involved in these cellular processes. Dietary nitrate provides a physiological substrate for nitric oxide production, which promotes vasodilatation, increases blood flow and lowers blood pressure. A brief narrative and critical review on dietary nitrate intake effects are addressed herein by considering vegetable sources, dosage, intervention regimen and cardioprotective effects achieved in both healthy and cardiovascular-susceptible individuals. Compared to other nitrate-rich vegetables, beets were proven to be the best choice for non-drug therapy because of their sensorial characteristics and easy formulations that facilitate patient adherence for long periods, allied to bioaccessibility and consequent effectiveness. Beets were shown to be effective in raising nitrate and nitrite in biological fluids at levels capable of promoting sustained improvement in primary and advanced hemodynamic parameters.